2017
DOI: 10.1152/ajpgi.00294.2016
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of microbiota within cecal crypts on the regenerative capacity of the intestinal epithelium following surgical stress

Abstract: This study provides novel insight into the process by which surgical injury places the intestinal epithelium at risk for colonization by pathogenic microbes and impairment of its regenerative capacity via loss of its microbiota. We show that fecal transplant restores crypt homeostasis in association with repopulation of the microbiota within cecal crypts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 34 publications
(50 reference statements)
2
19
0
Order By: Relevance
“…It appears that in the gut, cecal crypts devoid of their microbiota display loss of their regenerative capacity. 48 Whereas the gut has a relatively complicated niche structure, 49 the ocular surface may be less so and more accessible and may be an ideal place to investigate these interactions.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that in the gut, cecal crypts devoid of their microbiota display loss of their regenerative capacity. 48 Whereas the gut has a relatively complicated niche structure, 49 the ocular surface may be less so and more accessible and may be an ideal place to investigate these interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In DSS‐treated or IL‐10 −/− mice, the number of crypts invaded by bacteria increase upon inflammation despite concurrent thickening of the mucus layer 18 . In general, a higher number of crypts with bacteria is found in the proximal colon compared to the distal colon, which, in a healthy gut, might be also of physiological relevance, for example, for fermentation processes 18,20 . Whether this closer interaction of certain bacteria with the intestinal epithelium in the proximal colon might also foster inflammation and (colitis‐associated) tumor development, remains in debate.…”
Section: Introductionmentioning
confidence: 99%
“…Critical illness is characterized by loss of “health‐promoting” commensal bacteria and overgrowth of pathogenic bacteria, known as “dysbiosis.” 2 As the gut plays a key role in the progression of critical illness, overgrowth of pathogenic bacteria (dysbiosis) and acute loss of the colonization resistance of the microbiota may contribute to the development of new nosocomial infections, multiple‐organ dysfunction, and sepsis in intensive care unit (ICU) patients. Recently, in chronically critically ill patients, Zaborin et al 3 have found that normal intestinal microbiota becomes disrupted in response to host physiologic stress and antibiotic treatment. In fact, the composition of fecal samples revealed an overgrowth of Enterococcus , Staphylococcus , and the family Enterobacteriaceae, as well as the emergence of Candida species in a high percentage of patients 3 .…”
mentioning
confidence: 99%
“…Recently, in chronically critically ill patients, Zaborin et al 3 have found that normal intestinal microbiota becomes disrupted in response to host physiologic stress and antibiotic treatment. In fact, the composition of fecal samples revealed an overgrowth of Enterococcus , Staphylococcus , and the family Enterobacteriaceae, as well as the emergence of Candida species in a high percentage of patients 3 . Similarly, in a trial conducted at 4 centers in the United States and Canada, the ICU patient microbiome has been characterized 4 .…”
mentioning
confidence: 99%